The role of surface and structural functionalisation on graphene adsorbent nanomaterial for CO2 adsorption application : Recent progress and future prospects - Amirul Hafiiz, Ruhaimi; Che Ku Nor Liana, Che Ku Hitam; Muhammad Arif, Ab Aziz; Norul Hisham, A. Hamid; Herma Dina, Setiabudi; Teh, L. P. (Elsevier Ltd, 2022)
Recent progress in carbon dioxide (CO2) capture technologies using adsorption techniques has resulted in advances in the fabrication of solid adsorbents. Graphene (2D carbon-based category) nanomaterials have the potential for CO2 capture, owing to their abundantly available material sources, graphitic properties, sole porosity, stability, and cost-effectiveness. Graphene also demonstrates versatility toward numerous functionalisation and modification approaches with numerous agents. This significantly alters its physicochemical properties and adsorption capability, which will consequently improve the CO2 capture performance. Therefore, it is important to provide a review of the cutting-edge of graphene-based nanomaterial adsorbent studies on CO2 adsorption. This review covers various modification approaches, including surface functionalisation/modification (e.g., by using an amine, N-doping, and ionic liquid) and nanomaterial composite with other suitable materials and their effect on CO2 adsorption performance. A number of factors affecting CO2 capture behaviour are discussed thoroughly in order to gain a better understanding of the CO2 capture's enhancement mechanism. Furthermore, the direction for upcoming studies presented in this review are anticipated to guide the expansion of novel graphene-based CO2 capture systems.